2015
DOI: 10.1186/s12876-015-0290-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the usefulness of endoscopic papillary large-balloon dilation with endoscopic sphincterotomy for large and multiple common bile duct stones

Abstract: BackgroundEndoscopic sphincterotomy (EST) is currently recognized as the primary endoscopic treatment for common bile duct stones. However, it is difficult to remove multiple (≥3) or large (≥15 mm) common bile duct stones with EST alone. Recently, EST plus endoscopic papillary large-balloon dilation (EPLBD) was reported to be an effective treatment for such bile duct stones. We compared the results of EST and EST + EPLBD for multiple (≥3) or large (≥15 mm) stones that were difficult to treat using EST alone. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…In our study, both EST and EPLBD alone for management of bile duct stones resulted in similar outcomes with respect to complete stone clearance (100% versus 99.4%), which is similar to previous results regarding overall stone clearance [ 12 , 21 , 22 ]. In addition, ML might be used more often in the EST group compared to the EPLBD group for removal of large or multiple stones in our study (17 [28.3%] versus 29 [18%]).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, both EST and EPLBD alone for management of bile duct stones resulted in similar outcomes with respect to complete stone clearance (100% versus 99.4%), which is similar to previous results regarding overall stone clearance [ 12 , 21 , 22 ]. In addition, ML might be used more often in the EST group compared to the EPLBD group for removal of large or multiple stones in our study (17 [28.3%] versus 29 [18%]).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the success rate of the first-session treatment for ≥10- or ≥ 12-mm bile duct stone removal was 81.4–85% in the EST group [9, 16, 17], 65–89% in the EPLBD group [2, 10, 12, 16, 20, 21], and 71–97% in the EPLBD + EST group [2, 710, 17]. In particular, large bile duct stones ≥15 mm yielded an overall success rate of 88.9–100% for stone removal in the EST group, 97.35–100% in the EPLBD group, and 94.4–100% in the EPLBD + EST group [1, 3, 4, 14, 15, 18]. The success rates of the first-session treatment for ≥15-mm bile duct stone removal were 55.6–87% in the EST group, 78–87.87% in the EPLBD group, and 83–88.2% in the EPLBD + EST group [3, 4, 14, 15, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Although EPLBD was performed recently for patients with large CBDSs, the present study only included 3 patients who underwent EPLBD. Some previous studies reported that EPLBD with EST for large CBDSs was associated with an equal number (or fewer) ERCP-related complications to EST alone ( 7 , 21 ). Based on these previous studies, single-stage endoscopic stone removal with EPLBD may be a safe procedure for the removal of large CBDSs.…”
Section: Discussionmentioning
confidence: 95%
“…In approximately 90% of the cases, endoscopic stone removal is possible following EST and EPBD using a basket or balloon ( 3 , 4 ). For large common bile duct stones (CBDSs), endoscopic stone removal is achieved with a mechanical lithotripter ( 5 , 6 ) or endoscopic large balloon dilation (EPLBD) ( 7 ). Thus, endoscopic stone removal is increasingly used based on the high success rate.…”
Section: Introductionmentioning
confidence: 99%